Expanding the Isotopic Toolbox to Track Monarch Butterfly (Danaus plexippus) Origins and Migration: On the Utility of Stable Oxygen Isotope (δ18O) Measurements - Hobson, Keith A.; Kardynal, Kevin J.; Koehler, Geoff (Frontiers in Ecology and Evolution, 2019)
The measurement of naturally occurring stable hydrogen (δ2H) and carbon (δ13C) isotopes in wings of the eastern North American monarch butterflies (Danaus plexippus) have proven useful to infer natal origins of individuals overwintering in Mexico. This approach has provided a breakthrough for monarch conservation because it is the only viable means of inferring origins at continental scales. Recently, routine simultaneous analyses of tissue δ2H and δ18O of organic materials has emerged leading to questions of whether the dual measurement of these isotopes could be used to more accurately infer spatial origins even though the two isotopes are expected to be coupled due to the meteoric relationship. Such refinement would potentially increase the accuracy of isotopic assignment of wintering monarchs to natal origin. We measured a sample of 150 known natal-origin monarchs from throughout their eastern range simultaneously for both δ2H and δ18O wing values. Wing δ2H and δ18O values were correlated (r2=0.42). We found that wing δ2H values were more closely correlated with amount-weighted growing season average precipitation δ2H values predicted for natal sites (r2=0.61) compared to the relationship between wing δ18O values and amount-weighted growing season average precipitation δ18O values (r2=0.30). This suggests that monarch wing δ2H values will be generally more useful in natal assignments than δ18O values. Spatial information related to the use of deuterium excess in environmental waters was similarly found to be not useful when applied to monarch wings likely due to the considerable variance in wing δ18O values. Nonetheless, we recommend further testing of monarch wing δ2H and δ18O values from known natal sites with an emphasis on field data across a strong gradient in precipitation deuterium excess.